Passive listening to preferred motor tempo modulates corticospinal excitability - Michaelis, Kelly; Wiener, Martin; Thompson, James C. (Frontiers in Human Neuroscience, 2014)
Rhythms are an essential characteristic of our lives and auditory-motor coupling affects a variety of behaviors. Previous research has shown that neural regions associated with motor system processing are coupled to perceptual rhythmic processing, such that the perception of rhythmic stimuli can entrain motor responses. However, the degree to which individual preference modulates the motor system is unknown. Recent work has shown that passively listening to metrically strong rhythms increases corticospinal excitability, as indicated by transcranial magnetic stimulation (TMS). Furthermore, neuroimaging evidence suggests that premotor activity increases while listening to tempos occurring within a preferred tempo category. Preferred tempo (PT) refers to the rate of a hypothetical endogenous oscillator that may be indicated by spontaneous motor tempo (SMT) and preferred perceptual tempo (PPT) measurements. The present study investigated whether listening to a rhythm at an individual's PT preferentially modulates motor excitability. SMT was obtained in human participants through a tapping task, in which subjects were asked to tap a response key at their most comfortable rate. Subjects listened to tone sequences at 11 log-spaced tempos and rated their preference for each (PPT). SMT and PPT measurements were correlated, indicating that preferred and produced tempos occurred at a similar rate. Crucially, single-pulse TMS delivered to left M1 during PPT judgments revealed that corticospinal excitability, measured by motor-evoked potentials, was modulated by tempos traveling closer to individual PT. However, the specific nature of this modulation differed across individuals, with some exhibiting an increase in excitability around PT and others exhibiting a decrease. These findings suggest that auditory-motor coupling induced by rhythms is preferentially modulated by rhythms occurring at a preferred rate, and that individual differences can alter the nature of this coupling.